Supply Chain System Analysis in Single Vendor and Multi Retailer to Reduce Bullwhip Effect Using Vendor Managed Inventory (VMI) Method at Company X - Dira Ernawati; Yekti Condro Winursito (Nusantara Science and Technology Proceedings, 2023)
Company X, one of the largest dolomite fertilizer manufacturers in Indonesia, has recently encountered issues regarding discrepancies in information regarding demand and orders between the company and its eight sales offices. This problem mainly pertains to the Magnesium Fertilizer Magfertil 20+ product in 50 kg packaging. This situation has disrupted the company's supply chain and led to uncertainty in demand, commonly known as the bullwhip effect in the supply chain. The objective of this research is to achieve optimal inventory management to reduce the bullwhip effect among stakeholders in Company X's supply chain. The approach used is the Vendor Managed Inventory (VMI) method. The calculation results demonstrate that the implementation of the Vendor Managed Inventory (VMI) method has been highly successful in reducing the bullwhip effect at various levels within the supply chain. For instance, at the manufacturing level, the initial bullwhip effect value was 1.4503, but after implementing the VMI method, it significantly decreased to 0.4943. Meanwhile, the bullwhip effect I value at each sales office in Office Sales 1, Office Sales 2, Office Sales 3, Office Sales 4, Office Sales 5, Office Sales 6, Office Sales 7, Office Sales 8 is 1.4198, 1.4455, 1.6277, 1.4902, 1.3204, 1, 2093, 1.2994 and 1.4744. However, when applying the proposed VMI method the results of the bullwhip effect decreased drastically until the figures were 0.5007, 0.4773, 0.4909, 0.5097, 0.4975, 0.5015, 0.5014 and 0.4902.